Pengaruh CSR, Pertumbuhan Perusahaan, dan Media Exposure Terhadap Nilai Perusahaan pada Sektor Konsumer yang Terdaftar di BEI - Pinkan Kleofina; Virna Sulfitri (MANAJEMEN, 2026)
Firm value is one of the key indicators that reflects a company's success in increasing shareholder wealth. This study aims to provide empirical evidence on the effect of corporate social responsibility (CSR), firm growth, and media exposure on firm value as measured by Price to Book Value (PBV) in consumer non-cyclicals companies listed on the Indonesia Stock Exchange for the period 2022-2024. The sample was selected using purposive sampling and resulted in 241 panel data observations, which were analyzed using panel regression. The results show that CSR has no significant effect on firm value so the first hypothesis (HI) is rejected, while firm growth and media exposure have a positive and significant effect on firm value so the second (H2) and third (H3) hypotheses are accepted.